Innovative Technologies of Teaching Business French - K. Kuzmina, Elena; I. Nazarova, Gulnara; R. Nizamieva, Liliya; Leblanc, Cécile (International Journal of Engineering and Technology, 2018)
The article deals with the peculiarities of modern technologies in teaching professional French, taking into account the requirements of international examinations, specific language-learning needs of students and level of their language proficiency. Pedagogical technologies are demonstrated by the example of teaching business French in the sphere of tourism, hotel business, as well as the guide-interpreters training. The educational courses are aimed at the development of basic speaking skills and skills necessary for business communication in French. The developed pedagogical technology is based on French for specific purposes (FOS) methodology and cognitive-practical activity methods that allow to develop trainees’ communicative competence and their cognitive independence effectively. One of the conditions for successful development of communicative competence in the field of  business communication in a foreign language is to ensure that students do the necessary number of training exercises, in particular, connected with the use of business vocabulary, as well as with speaking exercises aimed at solving communication problems in real life situations of business communication. Similarity to the real life business environment is achieved through the use of information technologies and simulation games, which ultimately enhances the individual's ability to interact with others and adapt in the social and professional spheres of life. Successful completion of the end-of-course assessment is indicative of the fact that the students have reached high business communication competency.
Keywords: professional French; international examinations; pedagogical technologies; French for specific purposes; methods of cognitive-practical activity.